Campylobacter jejuni enters gut epithelial cells and impairs intestinal barrier function through cleavage of occludin by serine protease HtrA - Harrer, Aileen; Buecker, Roland; Böhm, Manja; Zarzecka, Urszula; Tegtmeyer, Nicole; Sticht, Heinrich; Schulzke, Joerg D.; Backert, Steffen (Gut Pathogens, 2019)
Campylobacter jejuni secretes HtrA (high temperature requirement protein A), a serine protease that is involved in virulence. Here, we investigated the interaction of HtrA with the host protein occludin, a tight junction strand component. Immunofluorescence studies demonstrated that infection of polarized intestinal Caco-2 cells with C. jejuni strain 81-176 resulted in a redistribution of occludin away from the tight junctions into the cytoplasm, an effect that was also observed in human biopsies during acute campylobacteriosis. Occludin knockout Caco-2 cells were generated by CRISPR/Cas9 technology. Inactivation of this gene affected the polarization of the cells in monolayers and transepithelial electrical resistance (TER) was reduced, compared to wild-type Caco-2 cells. Although tight junctions were still being formed, occludin deficiency resulted in a slight decrease of the tight junction plaque protein ZO-1, which was redistributed off the tight junction into the lateral plasma membrane. Adherence of C. jejuni to Caco-2 cell monolayers was similar between the occludin knockout compared to wild-type cells, but invasion was enhanced, indicating that deletion of occludin allowed larger numbers of bacteria to pass the tight junctions and to reach basal membranes to target the fibronectin receptor followed by cell entry. Finally, we discovered that purified C. jejuni HtrA cleaves recombinant occludin in vitro to release a 37 kDa carboxy-terminal fragment. The same cleavage fragment was observed in Western blots upon infection of polarized Caco-2 cells with wild-type C. jejuni, but not with isogenic Delta htrA mutants. HtrA cleavage was mapped to the second extracellular loop of occludin, and a putative cleavage site was identified. In conclusion, HtrA functions as a secreted protease targeting the tight junctions, which enables the bacteria by cleaving occludin and subcellular redistribution of other tight junction proteins to transmigrate using a paracellular mechanism and subsequently invade epithelial cells.
CRIS-Team WoS Importer:2019-03-06

Campylobacter jejuni serine protease HtrA plays an important role in heat tolerance, oxygen resistance, host cell adhesion, invasion, and transmigration. - Böhm, Manja; Lind, Judith; Backert, Steffen; Tegtmeyer, Nicole (European Journal of Microbiology and Immunology, 2015)
Campylobacter jejuni is an important pathogen of foodborne illness. Transmigration across the intestinal epithelial barrier and invasion are considered as primary reasons for tissue damage triggered by C. jejuni. Using knockout mutants, it was shown that the serine protease HtrA may be important for stress tolerance and physiology of C. jejuni. HtrA is also secreted in the extra-cellular environment, where it can cleave junctional host cell proteins such as E-cadherin. Aim of the present study was to establish a genetic complementation system in two C. jejuni strains in order to introduce the wild-type htrA gene in trans, test known htrA phenotypes, and provide the basis to perform further mutagenesis. We confirm that reexpression of the htrA wild-type gene in ΔhtrA mutants restored the following phenotypes: 1) C. jejuni growth at high temperature (44 °C), 2) growth under high oxygen stress conditions, 3) expression of proteolytically active HtrA oligomers, 4) secretion of HtrA into the supernatant, 5) cell attachment and invasion, and 6) transmigration across polarized epithelial cells. These results establish a genetic complementation system for htrA in C. jejuni, exclude polar effects in the ΔhtrA mutants, confirm important HtrA properties, and permit the discovery and dissection of new functions.

Establishment of serine protease htrA mutants in Helicobacter pylori is associated with secA mutations - Zawilak-Pawlik, Anna; Zarzecka, Urszula; Żyła-Uklejewicz, Dorota; Lach, Jakub; Strapagiel, Dominik; Tegtmeyer-Backert, Nicole; Böhm, Manja; Backert, Steffen; Skorko-Glonek, Joanna (Scientific Reports, 2019)
Helicobacter pylori plays an essential role in the pathogenesis of gastritis, peptic ulcer disease, and gastric cancer. The serine protease HtrA, an important secreted virulence factor, disrupts the gastric epithelium, which enables H. pylori to transmigrate across the epithelium and inject the oncogenic CagA protein into host cells. The function of periplasmic HtrA for the H. pylori cell is unknown, mainly due to unavailability of the htrA mutants. In fact, htrA has been described as an essential gene in this bacterium. We have screened 100 worldwide H. pylori isolates and show that only in the N6 strain it was possible to delete htrA or mutate the htrA gene to produce proteolytically inactive HtrA. We have sequenced the wild-type and mutant chromosomes and we found that inactivation of htrA is associated with mutations in SecA – a component of the Sec translocon apparatus used to translocate proteins from the cytoplasm into the periplasm. The cooperation of SecA and HtrA has been already suggested in Streptococcus pneumonia, in which these two proteins co-localize. Hence, our results pinpointing a potential functional relationship between HtrA and the Sec translocon in H. pylori possibly indicate for the more general mechanism responsible to maintain bacterial periplasmic homeostasis.
CRIS-Team Scopus Importer:2019-08-27

Expression of Helicobacter pylori serine protease HtrA in Campylobacter jejuni reveals a crucial function in oxygen stress resistance, heat tolerance and epithelial barrier disruption - Böhm, Manja; Tegtmeyer, Nicole; Harrer, Aileen; Skorko-Glonek, Joanna; Backert, Steffen (Journal of Cellular Immunology and Serum Biology, 2017)

Fragment-Based de Novo Design Reveals a Small-Molecule Inhibitor of Helicobacter Pylori HtrA - Perna, Anna M.; Rodrigues, Tiago; Schmidt, Thomas P.; Böhm, Manja; Stutz, Katharina; Reker, Daniel; Pfeiffer, Bernhard; Altmann, Karl-Heinz; Backert, Steffen; Wessler, Silja; Schneider, Gisbert (Angewandte Chemie International Edition, 2015)
Sustained identification of innovative chemical entities is key for the success of chemical biology and drug discovery. We report the fragment-based, computer-assisted de novo design of a small molecule inhibiting Helicobacter pylori HtrA protease. Molecular binding of the designed compound to HtrA was confirmed through biophysical methods, supporting its functional activity in vitro. Hit expansion led to the identification of the currently best-in-class HtrA inhibitor. The results obtained reinforce the validity of ligand-based de novo design and binding-kinetics-guided optimization for the efficient discovery of pioneering lead structures and prototyping drug-like chemical probes with tailored bioactivity.
Created from Fastlane, Scopus look-up
Keywords: biophysical methods; chemical biology; computer-assisted drug design; drug design; receptor-ligand interactions

Function of Serine Protease HtrA in the Lifecycle of the Foodborne Pathogen Campylobacter jejuni - Böhm, Manja; Simson, Daniel; Escher, Ulrike; Schmidt, Anna-Maria; Bereswill, Stefan; Tegtmeyer, Nicole; Backert, Steffen; Heimesaat, Markus M. (European Journal of Microbiology and Immunology, 2018)
Campylobacter jejuni is a major food-borne zoonotic pathogen, responsible for a large proportion of bacterial gastroenteritis cases, as well as Guillian-Barre and Miller-Fisher syndromes. During infection, tissue damage is mainly caused by bacteria invading epithelial cells and traversing the intestinal barrier. C. jejuni is able to enter the lamina propria and the bloodstream and may move into other organs, such as spleen, liver, or mesenteric lymph nodes. However, the involved molecular mechanisms are not fully understood. C. jejuni can transmigrate effectively across polarized intestinal epithelial cells mainly by the paracellular route using the serine protease high-temperature requirement A (HtrA). However, it appears that HtrA has a dual function, as it also acts as a chaperone, interacting with denatured or misfolded periplasmic proteins under stress conditions. Here, we review recent progress on the role of HtrA in C. jejuni pathogenesis. HtrA can be transported into the extracellular space and cleaves cell-to-cell junction factors, such as E-cadherin and probably others, disrupting the epithelial barrier and enabling paracellular transmigration of the bacteria. The secretion of HtrA is a newly discovered strategy also utilized by other pathogens. Thus, secreted HtrA proteases represent highly attractive targets for anti-bacterial treatment and may provide a suitable candidate for vaccine development.
Created from Fastlane, WoS look-up

Helicobacter pylori Employs a Unique Basolateral Type IV Secretion Mechanism for CagA Delivery - Tegtmeyer, Nicole; Wessler, Silja; Necchi, Vittorio; Rohde, Manfred; Harrer, Aileen; Rau, Tilman; Asche, Isabell; Böhm, Manja; Loessner, Holger; Figueiredo, Ceu; Naumann, Michael; Palmisano, Ralf; et al. (Cell Host & Microbe, 2017)
The Helicobacter pylori (Hp) type IV secretion system (T4SS) forms needle-like pili, whose binding to the integrin-?1 receptor results in injection of the CagA oncoprotein. However, the apical surface of epithelial cells is exposed to Hp, whereas integrins are basolateral receptors. Hence, the mechanism of CagA delivery into polarized gastric epithelial cells remains enigmatic. Here, we demonstrate that T4SS pilus formation during infection of polarized cells occurs predominantly at basolateral membranes, and not at apical sites. Hp accomplishes this by secreting another bacterial protein, the serine protease HtrA, which opens cell-to-cell junctions through cleaving epithelial junctional proteins including occludin, claudin-8, and E-cadherin. Using a genetic system expressing a peptide inhibitor, we demonstrate that HtrA activity is necessary for paracellular transmigration of Hp across polarized cell monolayers to reach basolateral membranes and inject CagA. The contribution of this unique signaling cascade to Hp pathogenesis is discussed.
EVALuna2:6906

HtrA-dependent adherence and invasion of Campylobacter jejuni in human vs. avian cells - Simson, Daniel; Böhm, Manja; Backert, Steffen (Letters in Applied Microbiology, 2020)

Human campylobacteriosis - Backert, Steffen; Tegtmeyer, Nicole; Croinin, Tadhg O.; Böhm, Manja; Heimesaat, Markus M. (Campylobacter: Features, Detection, and Prevention of Foodborne Disease, 2017)
Campylobacter subspecies represent a highly frequent cause of foodborne gastrointestinal (GI) illnesses in humans worldwide. The incidence and prevalence of campylobacteriosis due to infection with Campylobacter jejuni has increased over the past decades, both in developed and developing countries. The clinical outcome of C. jejuni infection ranges from mild to severe diarrheal disease, and some postinfection sequelae, including Guillain-Barré syndrome, reactive arthritis, and others. Poultry and poultry farms represent a major reservoir and source of transmission of C. jejuni strains to humans. Other risk factors of outbreaks include the consumption of contaminated meat, milk, vegetables, and water as well as direct contact with live animals or surface water. This Chapter highlights the various known routes of C. jejuni transmission and infection, bacterial, and host virulence determinants as well as their proposed role in the development of C. jejuni-mediated disease.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Campylobacteriosis; Guillain-Barré syndrome; Inflammatory bowel disease; Irritable bowel syndrome; Outbreak; Reactive arthritis; Reiter's syndrome

Identification of E-cadherin signature motifs functioning as cleavage sites for Helicobacter pylori HtrA - Schmidt, Thomas P.; Perna, Anna M.; Fugmann, Tim; Böhm, Manja; Hiss, Jan; Haller, Sarah; Goetz, Camilla; Tegtmeyer, Nicole; Hoy, Benjamin; Rau, Tilman; Neri, Dario; Backert, Steffen; et al. (Scientific Reports, 2016)
The cell adhesion protein and tumour suppressor E-cadherin exhibits important functions in the prevention of gastric cancer. As a class-I carcinogen, Helicobacter pylori (H. pylori) has developed a unique strategy to interfere with E-cadherin functions. In previous studies, we have demonstrated that H. pylori secretes the protease high temperature requirement A (HtrA) which cleaves off the E-cadherin ectodomain (NTF) on epithelial cells. This opens cell-to-cell junctions, allowing bacterial transmigration across the polarised epithelium. Here, we investigated the molecular mechanism of the HtrA-E-cadherin interaction and identified E-cadherin cleavage sites for HtrA. Mass-spectrometry-based proteomics and Edman degradation revealed three signature motifs containing the [VITA]-[VITA]-x-x-D-[DN] sequence pattern, which were preferentially cleaved by HtrA. Based on these sites, we developed a substrate-derived peptide inhibitor that selectively bound and inhibited HtrA, thereby blocking transmigration of H. pylori. The discovery of HtrA-targeted signature sites might further explain why we detected a stable 90 kDa NTF fragment during H. pylori infection, but also additional E-cadherin fragments ranging from 105 kDa to 48 kDa in in vitro cleavage experiments. In conclusion, HtrA targets E-cadherin signature sites that are accessible in in vitro reactions, but might be partially masked on epithelial cells through functional homophilic E-cadherin interactions.
EVALuna2:6912

Immunopathological properties of the Campylobacter jejuni flagellins and the adhesin CadF as assessed in a clinical murine infection model - Schmidt, Anna Maria; Escher, Ulrike; Mousavi, Soraya; Tegtmeyer, Nicole; Böhm, Manja; Backert, Steffen; Bereswill, Stefan; Heimesaat, Markus M. (Gut Pathogens, 2019)
Background: Campylobacter jejuni infections constitute serious threats to human health with increasing prevalences worldwide. Our knowledge regarding the molecular mechanisms underlying host-pathogen interactions is still limited. Our group has established a clinical C. jejuni infection model based on abiotic IL-10 -/- mice mimicking key features of human campylobacteriosis. In order to further validate this model for unraveling pathogen-host interactions mounting in acute disease, we here surveyed the immunopathological features of the important C. jejuni virulence factors FlaA and FlaB and the major adhesin CadF (Campylobacter adhesin to fibronectin), which play a role in bacterial motility, protein secretion and adhesion, respectively. Methods and results: Therefore, abiotic IL-10 -/- mice were perorally infected with C. jejuni strain 81-176 (WT) or with its isogenic flaA/B (ΔflaA/B) or cadF (ΔcadF) deletion mutants. Cultural analyses revealed that WT and ΔcadF but not ΔflaA/B bacteria stably colonized the stomach, duodenum and ileum, whereas all three strains were present in the colon at comparably high loads on day 6 post-infection. Remarkably, despite high colonic colonization densities, murine infection with the ΔflaA/B strain did not result in overt campylobacteriosis, whereas mice infected with ΔcadF or WT were suffering from acute enterocolitis at day 6 post-infection. These symptoms coincided with pronounced pro-inflammatory immune responses, not only in the intestinal tract, but also in other organs such as the liver and kidneys and were accompanied with systemic inflammatory responses as indicated by increased serum MCP-1 concentrations following C. jejuni ΔcadF or WT, but not ΔflaA/B strain infection. Conclusion: For the first time, our observations revealed that the C. jejuni flagellins A/B, but not adhesion mediated by CadF, are essential for inducing murine campylobacteriosis. Furthermore, the secondary abiotic IL-10 -/- infection model has been proven suitable not only for detailed investigations of immunological aspects of campylobacteriosis, but also for differential analyses of the roles of distinct C. jejuni virulence factors in induction and progression of disease.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Bacterial translocation; CadF; Campylobacter jejuni; Extra-intestinal immune responses; FlaA/B; Flagellin; Host-pathogen-interaction; IL-10; Intestinal immunopathology; Pro-inflammatory immune responses; Secondary abiotic (gnotobiotic) mice; Systemic immune responses

Overexpression of serine protease HtrA enhances disruption of adherens junctions, paracellular transmigration and type IV secretion of CagA by Helicobacter pylori - Harrer, Aileen; Böhm, Manja; Backert, Steffen; Tegtmeyer, Nicole (Gut Pathogens, 2017)
Background: The serine protease HtrA is an important factor for regulating stress responses and protein quality control in bacteria. In recent studies, we have demonstrated that the gastric pathogen Helicobacter pylori can secrete HtrA into the extracellular environment, where it cleaves-off the ectodomain of the tumor suppressor and adherens junction protein E-cadherin on gastric epithelial cells. Results: E-cadherin cleavage opens cell-to-cell junctions, allowing paracellular transmigration of the bacteria across polarized monolayers of MKN-28 and Caco-2 epithelial cells. However, rapid research progress on HtrA function is mainly hampered by the lack of ΔhtrA knockout mutants, suggesting that htrA may represent an essential gene in H. pylori. To circumvent this major handicap and to investigate the role of HtrA further, we overexpressed HtrA by introducing a second functional htrA gene copy in the chromosome and studied various virulence properties of the bacteria. The resulting data demonstrate that overexpression of HtrA in H. pylori gives rise to elevated rates of HtrA secretion, cleavage of E-cadherin, bacterial transmigration and delivery of the type IV secretion system (T4SS) effector protein CagA into polarized epithelial cells, but did not affect IL-8 chemokine production or the secretion of vacuolating cytotoxin VacA and γ-glutamyl-transpeptidase GGT. Conclusions: These data provide for the first time genetic evidence in H. pylori that HtrA is a novel major virulence factor controlling multiple pathogenic activities of this important microbe.
Created from Fastlane, Scopus look-up
Keywords: Abl; Adherens junction; CagA; E-cadherin; EPIYA; Helicobacter pylori; HtrA; Integrin; Protease; Src; T4SS; Tight junction; Transwell; Type IV secretion system

Protease Activity of Campylobacter jejuni HtrA Modulates Distinct Intestinal and Systemic Immune Responses in Infected Secondary Abiotic IL-10 Deficient Mice - Schmidt, Anna-Maria; Escher, Ulrike; Mousavi, Soraya; Böhm, Manja; Backert, Steffen; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Cellular and Infection Microbiology, 2019)
Even though human Campylobacter jejuni infections are progressively increasing worldwide, the underlying molecular mechanisms of pathogen-host-interactions are still not fully understood. We have recently shown that the secreted serine protease HtrA plays a key role in C. jejuni cellular invasion and transepithelial migration in vitro, and is involved in the onset of intestinal pathology in murine infection models in vivo. In the present study, we investigated whether the protease activity of HtrA had an impact in C. jejuni induced acute enterocolitis. For this purpose, we perorally infected secondary abiotic IL-10(-/-) mice with wildtype C. jejuni strain NCTC11168 (11168(WT))or isogenic bacteria carrying protease-inactive HtrA with a single point mutation at S197A in the active center (11168(HtrA-S197A)) Irrespective of the applied pathogenic strain, mice harbored similar C. jejuni loads in their feces and exhibited comparably severe macroscopic signs of acute enterocolitis at day 6 postinfection (p.i.). Interestingly, the 11168(HtrA-S197A) infected mice displayed less pronounced colonic apoptosis and immune cell responses, but enhanced epithelial proliferation as compared to the 11168(WT) strain infected controls. Furthermore, less distinct microscopic sequelae in 11168(HtrA-S197A) as compared to parental strain infected mice were accompanied by less distinct colonic secretion of pro-inflammatory cytokines such as MCP-1, IL-6, TNF, and IFN-gamma in the former as compared to the latter. Strikingly, the S197A point mutation was additionally associated with less pronounced systemic pro-inflammatory immune responses as assessed in serum samples. In conclusion, HtrA is a remarkable novel virulence determinant of C. jejuni, whose protease activity is not required for intestinal colonization and establishment of disease, but aggravates campylobacteriosis by triggering apoptosis and pro-inflammatory immune responses.
CRIS-Team WoS Importer:2019-04-12

The impact of serine protease HtrA in apoptosis, intestinal immune responses and extra-intestinal histopathology during Campylobacter jejuni infection of infant mice - Heimesaat, Markus M.; Fischer, Andre; Alutis, Marie; Grundmann, Ursula; Böhm, Manja; Tegtmeyer, Nicole; Goebel, Ulf B.; Kühl, Anja A.; Bereswill, Stefan; Backert, Steffen (Gut Pathogens, 2014)

The role of serine protease HtrA in acute ulcerative enterocolitis and extra-intestinal immune responses during Campylobacter jejuni infection of gnotobiotic IL-10 deficient mice - Heimesaat, Markus M.; Alutis, Marie; Grundmann, Ursula; Fischer, Andre; Tegtmeyer, Nicole; Böhm, Manja; Kuehl, Anja A.; Goebel, Ulf B.; Backert, Steffen; Bereswill, Stefan (Frontiers in Cellular and Infection Microbiology, 2014)
Campylobacter jejuni infections have a high prevalence worldwide and represent a significant socioeconomic burden. C. jejuni can cross the intestinal epithelial barrier as visualized in biopsies derived from human patients and animal models, however, the underlying molecular mechanisms and associated immunopathology are still not well understood. We have recently shown that the secreted serine protease HtrA (high temperature requirement A) plays a key role in C. jejuni cellular invasion and transmigration across polarized epithelial cells in vitro. In the present in vivo study we investigated the role of HtrA during C. jejuni infection of mice. We used the gnotobiotic IL-10-/- mouse model to study campylobacteriosis following peroral infection with the C. jejuni wild-type (WT) strain NCTC11168 and the isogenic, non-polar NCTC11168ΔhtrA deletion mutant. Six days post infection (p.i.) with either strain mice harbored comparable intestinal C. jejuni loads, whereas ulcerative enterocolitis was less pronounced in mice infected with the ΔhtrA mutant strain. Moreover, ΔhtrA mutant infected mice displayed lower apoptotic cell numbers in the large intestinal mucosa, less colonic accumulation of neutrophils, macrophages and monocytes, lower large intestinal nitric oxide, IFN-γ, and IL-6 as well as lower TNF-α and IL-6 serum concentrations as compared to WT strain infected mice at day 6 p.i. Notably, immunopathological responses were not restricted to the intestinal tract given that liver and kidneys exhibited mild histopathological changes 6 days p.i. with either C. jejuni strain. We also found that hepatic and renal nitric oxide levels or renal TNF-α concentrations were lower in the ΔhtrA mutant as compared to WT strain infected mice. In conclusion, we show here that the C. jejuni HtrA protein plays a pivotal role in inducing host cell apoptosis and immunopathology during murine campylobacteriosis in the gut in vivo.
Created from Fastlane, Scopus look-up
Keywords: Bacterial translocation; Colonization resistance; Extra-intestinal immune responses; Host-pathogen-interaction; Innate immunity; Intestinal immunopathology; Systemic immune responses; Ulcerative enterocolitis

Transmigration route of Campylobacter jejuni across polarized intestinal epithelial cells: Paracellular, transcellular or both? - Backert, Steffen; Böhm, Manja; Wessler, Silja; Tegtmeyer, Nicole (Cell Communication and Signaling, 2013)
Intact intercellular junctions and cellular matrix contacts are crucial structural components for the formation and maintenance of epithelial barrier functions in humans to control the commensal flora and protect against intruding microbes. Campylobacter jejuni is one of the most important zoonotic pathogens causing food-borne gastroenteritis and potentially more severe diseases such as reactive arthritis or Guillain-Barré syndrome. Crossing the intestinal epithelial barrier and host cell invasion by C. jejuni are considered to represent the primary reasons of gut tissue damage in humans and various animal model systems including monkeys, piglets, rabbits, hamsters and ferrets. C. jejuni is also able to invade underlying tissues such as the lamina propria, can enter the bloodstream, and possibly reach distinct organs such as spleen, liver or mesenteric lymph nodes. However, the molecular mechanisms as well as major bacterial and host cell factors involved in these activities are poorly understood. Various models exist by which the pathogen can trigger its own transmigration across polarized intestinal epithelial cells in vitro, the paracellular and/or transcellular mechanism. Recent studies suggest that bacterial factors such as flagellum, serine protease HtrA and lipooligosaccharide LOS may play an active role in bacterial transmigration. Here we review our knowledge on transmigration of C. jejuni as well as some other Campylobacter species, and discuss the pros and cons for the route(s) taken to travel across polarized epithelial cell monolayers. These studies provide fresh insights into the infection strategies employed by this important pathogen. © 2013 Backert et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Adherens junctions; Cell polarity; Cellular invasion; E-cadherin; Fibronectin; HtrA; Integrins; Invasion; Molecular pathogenesis; Signaling; TER; Tight junctions; Transmigration; Virulence